More of a Father, or More of an Employee? The Conditions of Working Men Raising Children in Poland - Kotowska-Wójcik, Olga; Luty-Michalak, Marta (Information & Media, 2018)
[full article, abstract in English; abstract in Lithuanian]The qualitative study, conducted in 2016, was divised to explore the respondents’ perceptions on balance between their roles as employees and as parents, as well as the similarities and differences between their expectations and experiences. Using data collected from semi-structured, single-person interviews with 27 fathers of young children, living in Warsaw, Poland, we identify and explore ways in which the participants construct their description of the work-life balance, especially in the perspective of family obligations.By analyzing the data on the work-life balance, our study makes a unique contribution to the literature by drawing attention to the circumstances of how fathers deal with everyday decisions, some living in families with partnership relations, and how it pertains to their attitudes in terms of being fathers while failing or managing the work-life balance. The moment of family life cycle (e.g. just married couple, couple with small children, couple with teenagers, etc.) particularly the experiences of fatherhood, illustrates the different narratives of respondents. Our findings show the demand for implementing more flexibility of work into the employment market, which is especially important for parents.SummaryA qualitative research, conducted as a pilot study titled The Contemporary Father – at the Crossroads of Expectations and Reality, was conducted in Warsaw in 2017. The data analysis showed that fathers with full families (husband, wife and children) do express their willingness to participate in their family lives, and especially to spend time with their children. On the other hand, most of the respondents pointed out that their main responsibility is to provide the financial security of their families, so being active at the employment market is very important for them. Meanwhile, most of the fathers expressed satisfaction from having wives/partners that are also actively employed. Fathers face difficulties in achieving a work-life balance in their lives, as the dual model of having both a career and a family seems to be the most appropriate for them. The findings show that the respondents face the constant dilemma of having to choose where to devote their time – to the family or the workplace.
Keywords: fathering,; professional life; work-life balance; employment models; Poland.